The Relationship Between Cigarette Smoke Exposure With Acute Respiratory Infections (ARI) And Stunting In Bima 2022 - Nurul Qamarya; Zahratul Hayati (Science Midwifery, 2022)
Respiratory infections are the single largest infectious cause of death in children worldwide. Respiratory infections killed 808,694 children under 5 years of age in 2017, accounting for 15% of all deaths of children under five years of age. Toddlers who have poor nutritional status have a 4.1 times greater chance of experiencing Acute Respiratory Infections (ARI) than children under five with good nutritional status. Malnutrition status is also a major factor in the high incidence of stunting that occurs since the baby is still in the womb until the early days after the baby is born. ARI and stunting are known to be diseases and developmental disorders, one of which is cigarette smoke, because they can interfere with the absorption function of children's nutrition, congenital abnormalities and low birth weight. The smoking behavior and habits of parents in the house make all residents of the house and toddlers passive smokers who are always exposed to cigarette smoke at any time and every day. Parents who have the habit of smoking in the house have the opportunity to increase the incidence of ARI in their toddlers by 7.83 times compared to the homes of toddlers whose parents do not smoke in the house. This study aims to determine the relationship between exposure to cigarette smoke and the incidence of ARI and stunting in children under five in the city of Bima in 2022 . This type of research is quantitative, using a cross sectional approach. The population in this study were all mothers who had toddlers in the working area of the Puskesmas in Bima City. The number of samples is 100 mothers who have toddlers. The sampling technique used purposive sampling. Collecting data using a questionnaire, univariate and bivariate data analysis with Chi Square statistical test.The results obtained from this study were that most of the toddlers experienced Upper Acute Respiratory Infections (ARI) (ARI), namely (86%), Toddlers who experienced stunting, namely ( 6%). Toddlers who are exposed to cigarette smoke and have ARI are 75.6% and those who are not exposed to cigarette smoke and have ARI are 94.5%. The results of the chi square test obtained a P value of 0.006 meaning that there is a relationship between exposure to cigarette smoke and the incidence of ARI in toddlers. The results of the Odds Ratio (OR) 95% CI = 0.178 means that toddlers who are exposed to cigarette smoke are 0.178 times more likely to experience ARI than toddlers who are not exposed to cigarette smoke. Toddlers who are exposed to cigarette smoke and experience stunting are 13.3% and those who are not exposed to cigarette smoke and experience stunting are 0%. The results of the chi square test obtained a P value of 0.007 meaning that there is a relationship between exposure to cigarette smoke and the incidence of stunting in toddlers with Odds values Ratio (OR) 95%CI = 0.867 means that toddlers who are exposed to cigarette smoke have a 0.867 times greater chance of experiencing stunting than those who are not exposed to cigarette smoke. Toddlers who experienced ARI and also experienced stunting were 2.3% and those who did not experience ARI but experienced stunting were 28.6%. The results of the chi square test obtained a P value of 0.003 which means that there is a relationship between toddlers who have or are currently experiencing ARI with stunting. The Odds Ratio (OR) 95%CI = 0.060 means that toddlers with ARI have a 0.060 times greater chance of experiencing stunting than those without ARI. The results of this study are expected to be able to improve health behavior in the family and community environment as well as become the government's foothold in health promotion about smoke-free areas in order to realize the improvement and improvement of children's health status.